One‐Year Treatment Outcomes of Secukinumab Versus Tumor Necrosis Factor Inhibitors in Spondyloarthritis: Results From Five Nordic Biologic Registries Including More Than 10, 000 Treatment Courses. Issue 5 (8th March 2022) - Glintborg, Bente; Lindström, Ulf; Giuseppe, Daniela Di; Provan, Sella Aarrestad; Gudbjornsson, Bjorn; Hetland, Merete Lund; Michelsen, Brigitte; Wallman, Johan K.; Aaltonen, Kalle; Hokkanen, Anna‐Mari; Nordström, Dan; Jørgensen, Tanja Schjødt; et al.
Abstract : Objective: To describe baseline characteristics and to compare treatment effectiveness of secukinumab versus tumor necrosis factor inhibitors (TNFi) in patients with spondyloarthritis (SpA) using adalimumab as the main comparator. Methods: This was an observational, prospective cohort study. Patients with SpA (clinical ankylosing spondylitis, nonradiographic axial SpA, or undifferentiated SpA) starting secukinumab or a TNFi during 2015–2018 were identified from 5 Nordic clinical rheumatology registries. Data on comorbidities and extraarticular manifestations (psoriasis, uveitis, and inflammatory bowel disease) were captured from national registries (data available in 94% of patients) and included in multivariable analyses. We assessed 1‐year treatment retention (crude survival curves, adjusted hazard ratios [HRadj ] for treatment discontinuation) and 6‐month response rates (Ankylosing Spondylitis Disease Activity Score [ASDAS] score <2.1, Bath Ankylosing Spondylitis Disease Activity Index [BASDAI] <40 mm, crude/LUNDEX‐adjusted, adjusted logistic regression analyses with odds ratios [ORs]) stratified by line of biologic treatment (first, second, and third plus). Results: In total, 10, 853 treatment courses (842 secukinumab and 10, 011 TNFi, of which 1, 977 were adalimumab) were included. The proportions of patients treated with secukinumab during the first, second, and third‐plus lines of treatment were 1%, 6%, and 22%, respectively). Extraarticular manifestations varied across treatments, while other baseline characteristics were largely similar. Secukinumab had a 1‐year retention comparable to adalimumab as a first or second line of treatment but poorer as a third‐plus line of therapy (secukinumab 56% [95% confidence interval (95% CI) 51–61%] versus adalimumab 70% [95% CI 64–75%]; HRadj 1.43 [95% CI 1.12–1.81]). Across treatment lines, secukinumab had poorer estimates for 6‐month response rates than adalimumab, statistically significantly only for the third‐plus line (adjusted analyses: ASDAS score <2.1 OR 0.56 [95% CI 0.35–0.90]; BASDAI <40 mm OR 0.62 [95% CI 0.41–0.95]). Treatment outcomes varied across the 5 TNFi. Conclusion: Secukinumab was mainly used in biologics‐experienced patients with SpA. Secukinumab and adalimumab performed similarly in patients who had failed a first biologic, although with increasing prior biologic exposure, adalimumab was superior.